An empirical investigation into different stakeholder groups perception of project success. Issue 4 (May 2017) - Davis, Kate
Abstract: Organizations use projects to manage customized, one-off events across a wide range of functions. Project management is an essential operational tool and process that is utilized to effectively and efficiently manage resources, tasks and activities, and associated timelines. The purpose of this paper is to investigate the possibility that failure is a result of different interpretations of the criteria and factors used for success by multiple stakeholder groups. Currently, there is no recorded theory to determine project success within the project management literature, which includes both the perspective of multiple stakeholder groups and shared use of success dimensions for a given project. This omission is the basis of the current work, which explores the impact of using all stakeholder views as opposed to a selected few to define project success. The research outcomes are important for informed managerial decision making that enables the minimization of major financial losses. Highlights: An empirical paper investigating project success and stakeholders. Identifies a measurement method for stakeholder groups' perceptions of project success. Provides areas for survey analysis: benefit to the stakeholder group, time/cost/quality and accountability.